Road Defect Assessment Algorithm on Flexible Pavement - Ida Ayu Ari Angreni; Diyanti Diyanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the condition of road pavement mechanically which requires large, time-consuming, impractical, and can only identify one type of road damage. The development of digital technology, then identifying the type of damage can be done with an algorithm or method to detect and analyze the type of road damage quickly and accurately. The purpose of the study is to identify the value of road damage with the visual method of Dirgolaksono and Mochtar, create a model of a road damage assessment algorithm based on digital imagery, and apply the digital image method to the road section being reviewed. The research method with the initial step of the algorithm process is taking pictures using a type of digital camera, so that a digital image is produced which is then processed using Matlab R2016a. The results obtained are the classification of road damage and the damage value of the road section obtained by visual road damage and digital imagery accurately. Validation is carried out with a strong correlation between visual and digital damage, which means that there is no difference between the visual damage value and the digital image damage value